Manipulation of leaf senescence and chlorophyll degradation aiming fruit improvement - Lira, Bruno Silvestre (2017)
Leaves are responsible for the majority of the fixed carbon in most plant species. Along leaf development, the photosynthetic capacity increases until the organ reaches maturity. Consequently, at the onset of senescence the leaves have the highest photosynthetic activity, then, as the chloroplasts are dismantled and the photosynthetic machinery is degraded, leaves gradually lose the rate of carbon assimilation. Although the capacity to fix carbon declines as senescence progresses, nutrient remobilization from macromolecule degradation nourishes the developing sink organs. In this regard, delaying leaf senescence stands out as a promising strategy to increase plant yield as extends the window of time with maximum carbon fixation rate. Another approach that is receiving much attention is the manipulation of chlorophyll degradation once it potentially regulates photosynthetic capacity and affects the nutritional quality of harvestable organs. As chlorophyll is degraded, the released phytol is recycled and can be either stored (i.e. as fatty acid phytyl esters), used for chlorophyll synthesis or be incorporated in tocopherol biosynthesis. Tocopherols have high nutraceutical value due to their antioxidant properties. However, the majority of the studies regarding senescence and chlorophyll degradation were carried out in the model plant Arabidopsis thaliana or grasses, creating a knowledge gap about these processes in fleshy fruit-bearing plants of human diet interest. In this regard, the tomato, Solanum lycopersicum, is an excellent model not only for the genetic and genomic resources, but also for its agronomic and nutritional importance. Thus, this project aims to extend what is known about the effects of chlorophyll degradation and senescence manipulation over the metabolism and yield of tomato plants, as well as fruit nutritional quality. In order to evaluate the consequences of alteration in chlorophyll degradation, first the enzymes chlorophyllase and pheophytinase, both capable of dephytylating the chlorophyll molecule, were identified and characterised. An extensive phylogenetic, evolutive and transcriptional analysis allowed the identification of two groups of chlorophyllases, one putatively involved in the response to different stimuli, while the other may act in chlorophyll homeostasis. As for pheophytinase, only one group was identified, being related to physiologically programmed processes that trigger chlorophyll degradation (i.e. leaf senescence and fruit ripening). Given this scenario, pheophytinase was chosen to be constitutively knocked-down in order to evaluate the effects over the metabolism of leaves and fruits. As consequence of this manipulation, transgenic plants were impaired in the leaf senescence-associated chlorophyll breakdown, but, although with an initial delay, fruit ripening-associated degreening was not compromised. Several photosynthetic and biochemical parameters were signs of photoinhibition, possibly due to a deficiency in chlorophyll recycling in leaves. This led to an increase in sugar exportation towards fruits, ultimately increasing soluble sugar content of ripe fruits. However, as a consequence, carotenoid levels were reduced, what, at least partially, it was compensated by an increase in tocopherol content. The results indicated that pheophytinase plays a role beyond senescence-associated chlorophyll degradation and its manipulation led to the development of fruit with increased soluble sugars and tocopherols at the cost of lowering carotenoid levels. Thus, these evidences support the manipulation of chlorophyll breakdown as a strategy for improvement of fleshy fruit plants. In order to address the effects of senescence over yield and fruit quality, the transcription factor ORESARA1, which has been widely characterised in A. thaliana and is considered a key regulator of senescence initiation, was targeted. After a comprehensive phylogenetic analysis and the characterization of the regulatory mechanisms, one putative ortholog was selected to be silenced. As consequence of this manipulation, leaves displayed increased chlorophyll content. Moreover, as senescence was delayed, the extent of photosynthetic activity of the leaves was also expanded. As the number of fruits was increased in the knockdown lines, this reflected in an increment in the harvest index. Ripe fruits accumulated more soluble sugars and tocopherols. Collectively, the results support the manipulation of leaf senescence as a strategy for tomato yield improvement. Altogether, data obtained enhance the knowledge about the impacts of chlorophyll degradation and leaf senescence over the metabolism of fleshy-fruit plants, providing strategies to increase yield and nutritional quality of fruits